MOTIVASI PESERTA DIDIK UNTUK MENGIKUTI PENDIDIKAN DI SMP PASIR GANTING KECAMATAN PANCUNG SOAL KABUPATN PESISIR SELATAN - Karmila, Fani; Syarif, Mellyarti; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problems that exist in this students is how the image of motivation of learners to participate in education in junior Sand Ganting. Dilator research background by several things including learners often come late to school, often unplug / truant during the process of learning and not do the work, often noisier when lessons take place, no matter who criticize the teacher so many students live classes and finally the students are not longer in school. In addition, the students were allowed to work by the parents rather than the school. So, they prefer to work rather than take part in education. It is based on the lack of motivation of the learner, such as interest, attention and perseverance, while the external self-learners, such as school environment, family and community environment.This students aimed to describe the motivation of learners to participate in education at Sub Junior Ganting Sand Problem strike the South Coastal District as seen from within the individual (intrinsic) and external views of the individual (extrinsic) type of research is research in population and descriptive. Number of sample of 63 people. Means of data collection in this student was a questionnaire, and data analysis techniques in this study using a percentage formula. The results revealed a picture of motivation of learners to participate in education in terms of intrinsic criteria are at high (68.8%) and had increased again and the motivation of learners to participate in education in terms of extrinsic criteria for arriving at a high (58.7%). So,the motivation of learners to participate in education in junior high category Ganting sand.Based on the findings of the study suggested the supervising teacher and all teachers, especially to parents positive can provide encouragement to students, so that motivation is in self-learners can be improved because of the encouragement given to students can be improved, because the impetus given to learners want to learn more passion and motivation to improve the education that comes from the individual.